SELF-CONCEPT AND INTERPERSONAL COMMUNICATION PREDICTING HAPPINESS AT WORK OF EMPLOYEES IN COMMERCIAL BANKS - Ruanphaksat, Chaiwat; Pathanapakdee, Nontirat (CENTRAL ASIA AND THE CAUCASUS, 2021)
This research aims to 1) study level of self-concept, interpersonal communication and happiness at work of employees in commercial banks, 2) study the relation between self-concept and happiness at work of employees in commercial banks, 3) study relation between interpersonal communication and happiness at work of employees in commercial banks and 4) predict happiness at work of employees in commercial banks via self-concept and interpersonal communication. The sample group in this study were 435 employees from 2 commercial banks (N= 435). The statistics used in data analysis were percentage, mean, Standard Deviation, Pearson products moment correlation coefficient, Stepwise multiple regression analysis and partial correlation.The results showed that 1) generally, happiness at work of employees in commercial banks has got very high mean (xˉ = 3.92, SD = 0.26), self-concept of employees in commercial banks has got high level mean (xˉ = 4.00, SD = 0.26) and interpersonal communication of employees in commercial banks has got high level mean (xˉ = 4.15, SD = 0.25), 2) self-concept is related to happiness at work of employees in commercial banks with the statistically significant level at .01 and the high relation level of (r=0.83), 3) interpersonal communication has a connection to happiness at work of employees in commercial banks with the statistically significant level at .01 and the high relation level of (r=0.63) and 4) self-concept and interpersonal communication can predict happiness at work of employees in commercial banks with the percentage of 53.00.